Tindak Tutur pada Tradisi Mappettuada Suku Bugis (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
This study aims to The purpose of this study is to understand and describe locutionary, illocutionary, and perlocutionary speech acts in the Mappettuada tradition of the Bugis-Makassar ethnic group. The data in the study are in the form of linguistic units consisting of words, phrases, clauses, sentences of speech in the Bugis tribe's mappettuada tradition in online media (youtube). The results of the study revealed that the communication pattern of the Bugis tribe's mappettuada tradition is formed by the communication structure in a speech event between the speaker and the speech partner. The data in this study amounted to 29 data which were classified based on pragmatic theory, namely locutionary, illocutionary and perlocutionary speech acts. Locutionary speech acts were found in three forms of speech acts in the form of 2 declarative data, 2 interrogative data, and 2 imperative data. This proves that locutionary speech acts greatly influence the conversation process in the form of negotiations in determining the amount of money in the mappettu event. Illocutionary speech acts consist of 5 types, namely assertive speech acts with 4 data, directive 8 data, expressive 4 data, commissive 1 data, declarative 4 data. The assertive speech acts found consist of four forms of speech, namely mentioning, showing, informing and stating. The directive speech acts found consist of five forms of speech, namely inviting, requesting, charging, suggesting, and challenging. The expressive speech acts consist of three forms of speech, namely saying thank you, blaming and flattering. The commissive speech acts found consist of two forms of speech, namely swearing and promising. The declarative speech acts consist of four forms of speech, namely deciding, canceling, prohibiting, and granting. The most dominant speech act found in the interaction of the mappettu event is the directive speech act. In the perlocutionary speech act, data was found on two types of perlocutionary speech acts found, namely invitation speech acts and orders. In addition, there are also reactions or responses from the interlocutor when hearing the speech. The responses or reactions that arise include happiness, being more motivated, the effect of accepting the invitation, being more enthusiastic, immediately carrying out orders and so on.